Mobile telephony and broadcasting: are they compatible for consumers. (5th January 2005) - Picard, Robert G.
This paper explores the potential for audio and video services streamed to mobile handset from the perspective of consumer behaviour. The author argues that consumer choice rather than technology or supply side activities will determine the success of the services and that demand for mobile broadcasting services will come primarily from consumers who are currently using mobile audio and video services with other technologies. The author argues that increased attention needs to be placed on pressing issues as mobile communications capabilities increase and that a wide range of factors will influence consumer demand for mobile services.